Prevalência, riqueza e sazonalidade de hemosporídeos aviários e diferentes estágios de sucessão ecológica no Parque Estadual da Mata Seca, Minas Gerais, Brasil - Francisco Carlos Ferreira Junior (2016)
Environmental changes, such as land conversion for livestock farming, constitute the main causes of loss of biodiversity. These effects together can increase parasitic diseases risk in human and wildlife populations. Avian haemosporidian is a worldwide protozoan disease caused by parasites in the genera Plasmodium and Haemoproteus that has varying deleterious effects on free-living birds. Recent studies have revealed a considerable diversity of haemosporidians in Brazil, depicting this parasite-vector-host system as an important model for ecological and evolutionary studies of parasites of conservational value. Patterns in haemosporidian prevalence and diversity change between habitats with different levels of forest integrity. However, such parameters had not been accessed in forest fragments under different stages of ecological succession in Brazil. Little is known about haemosporidian vectors in the world, and even less is understood in Brazil. With that, we accessed the effects of the ecological succession in bird communities and in the prevalence and diversity of haemosporidians in birds and in mosquitos captured in Mata Seca State Park, Minas Gerais, which ecosystem is dominated by Seasonally Dry Tropical Forest. We mist-netted birds in four different successional stages: pasture areas, and early, intermediate, and late stages. The first three stages consisted in pasture areas abandoned 8, 12 and 30 years ago, respectively, and the late stage does not have reports of human intervention for more than 50 years. Seasonal effects on birds, mosquitos and parasite distribution were evaluated by conducting bird and mosquito captures at four periods: end of the rainy season, beginning and end of the dry season, and peak of the following rainy season. We captured 461 birds, which communities changed between pasture areas and the remaining successional stages. Haemosporidian prevalence, as detected by PCR, was higher within birds in pasture compared with birds captured in non-pasture areas when we considered whole communities. Prevalence also was higher within bird species captured exclusively in pasture areas then within species exclusive from non-pasture areas. Our results reveal that species exclusive from pasture areas increase haemosporidian infection risks for species that inhabit different successional stages when they include pasture areas in their range. Haemosporidian prevalence increased between the beginning and the end of the dry season, suggesting a phenomenon known as spring relapse, which has been reported in temperate latitudes, but that has never been detected in tropical areas. We also found seasonal changes in the distribution of Parahaemoproteus parasites. This subgenus was detected only during the rainy seasons. We used PCR and detected Plasmodium parasites in abdomen pools from the mosquito species Mansonia titillans and Ma. pseudotitillans, pointing them as putative vectors of avian malaria. The present study shows effects of ecological succession on the structure of bird communities. Species and individuals that inhabit advanced stages are benefited by presenting lower rates of infection by pathogenic parasites. Future studies targeting periodic and long-term samplings in other seasonal tropical environments will reveal if our results are due to random variation or if they reflect seasonal changes in haemosporidian infection in tropical birds.